Genome-Wide Identification and Abiotic Stress Response Analysis of C2H2 Zinc Finger Protein Genes in Foxtail Millet (Setaria italica) - Qian Zhao; Yingxin Zhang; Xiangyu Xing; Shuyao Li; Ruidong Sun; Weilong Zhang; Jun Zhang; Liangyu Jiang; Zhenyuan Zang; Ming Gao; Jian Zhang (Agronomy, 2025)
C2H2 zinc finger proteins (C2H2-ZFPs) constitute one of the largest transcription factor families in plants, playing crucial roles in growth, development, and stress responses. Here, we performed a comprehensive genome-wide analysis of C2H2-ZFPs in foxtail millet (Setaria italica v2.0), identifying 67 members that were unevenly distributed across all nine chromosomes. Most SiC2H2 proteins were predicted to be alkaline, stable, and nuclear-localized, with the exception of SiC2H2-11 and SiC2H2-66, which were chloroplast-targeted. Phylogenetic analysis with Arabidopsis thaliana and Oryza sativa (rice) homologs classified these genes into seven distinct subfamilies, each containing the characteristic motif1 domain. Evolutionary studies revealed 14 segmental duplication events and strong syntenic conservation with Triticum aestivum (wheat, 163 orthologous pairs), suggesting conserved functions during evolution. Promoter analysis identified multiple cis-acting elements associated with light responsiveness, hormone signaling, and stress adaptation. Transcriptome profiling and qPCR validation in the YuGu 56 cultivar identified several stress-responsive candidates, including SiC2H2-35 and SiC2H2-58 (salt tolerance), as well as SiC2H2-23 (5.19-fold induction under salt stress) and SiC2H2-32 (5.47-fold induction under drought). This study provides some valuable insights into the C2H2-ZFP family in foxtail millet and highlights potential genetic markers for improving stress resilience through molecular breeding approaches.